A political perspective on dance movement psychotherapy on interdisciplinary pathways: are we finding or losing our way?*. Issue 4 (2nd October 2017) - Eberhard-Kaechele, Marianne
Abstract: The phenomenon of interdisciplinarity is a global trend in many areas of research and health care. The article focusses on implications for dance movement psychotherapy on four different levels of the politics of the profession, and presents four types of individual interdisciplinary integration. Positive and negative aspects are considered, and solutions for problems suggested.